Tribological characteristics of as-cast A356/10wt.% SiCp functionally graded composite dry sliding against EN-31 steel under unidirectional and oscillatory modes. Issue 1 (March 2020) - Prem Kumar, J; Rajeev, V R; Krishnakumar, K; Hashim, M
Abstract: A comparison in tribological response characteristics of as-cast Al-SiCp functionally graded composite material (FGM) dry sliding against hardened EN-31 steel under unidirectional and oscillatory sliding modes was investigated for a sliding/oscillating velocity of 0.4m/s slid through 500m utilizing a pin-on-disc configuration. The A356/10 wt.% SiCp FGM was prepared using vertical centrifugal casting technique. The microstructure characterization was done by Leica optical microscope, and the microstructural analysis revealed the presence of different zones due to the radial gradient distribution of SiCp reinforcement. The hardness variation was found to have a good correlation with its microstructural features at different zones of FGM. Wear loss against load curve indicated an increase in trend for both sliding modes, whereas the coefficient of friction versus load plot showed a decreasing trend for both cases under an identical set of operating parameters. Further, oscillatory wear loss of FGM/EN-31 steel tribopair was observed to be higher in comparison with unidirectional sliding mode for the entire load range, (30-150N) investigated. At the same time, the coefficient of friction of tribopair in oscillatory sliding mode was found to lower than the unidirectional mode.